The Correlation between Students’ Reading Anxiety and Their Reading Ability - Munir, Sirajul; Suzanne, Nina; Fitri , Hidayatul (Ahmad Dahlan Journal of English Studies, 2023)
The objective of this research is to determine whether there is a correlation between students’ reading anxiety and their reading ability. This research is a correlational study. The population of this research were the 66 students of the English Teaching Department at UIN Mahmud Yunus Batusangkar. The sample was chosen by simple random sampling technique using Slovin’s formula. As a result, 55 students were used as a sample. The data were gathered by using questionnaires and reading test. The result of this research indicates that there was a correlation between students’ reading anxiety and their reading ability. It is indicated by the data analysis using the “r” product moment formula. The result shows that the calculated correlation coefficient (rxy) was -0.343 which has a negative sign, which means “rxy” has a negative direction. Next, “rxy” (-0.343) with degree of freedom (df)= N-2 (56-2) = 54. It can be stated that the r-table was 0.254 at the level significant 5%. It can be concluded that Ha was accepted because r-calculated (-0.343) was higher than the value of the r-table (0.254).